2011
DOI: 10.12659/msm.881387
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic encephalopathy: An updated approach from pathogenesis to treatment

Abstract: SummaryOne of the most serious complications of chronic or fulminant liver failure is hepatic encephalopathy (HE), associated most commonly with cirrhosis. In the presence of chronic liver disease, HE is a sign of decompensation, while in fulminant liver failure its development represents a worrying sign and usually indicates that transplantation will be required. Despite the significance of HE in the course of liver disease, the progress in development of new therapeutic options has been unremarkable over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 93 publications
(102 reference statements)
0
15
0
2
Order By: Relevance
“…Hepatic function insufficiency and short-circuit of circulation are key causes to the patients with chronic liver disease-induced type C HE, then accumulated toxins will circulate into the brain via the altered BBB and causes encephalopathy by abnormal neurotransmissions. At present, most scholars believe deregulated liver functions and impaired CNS functions can influence each other, resulting in secondary damages to the body [3,37] . Recent study found that increased activity of brain acetylcholinesterase in patients and animals of type C HE would cause the decrease of acetylcholine level.…”
Section: Type C He: Animal Models and Pathogenic Mechanismsmentioning
confidence: 99%
“…Hepatic function insufficiency and short-circuit of circulation are key causes to the patients with chronic liver disease-induced type C HE, then accumulated toxins will circulate into the brain via the altered BBB and causes encephalopathy by abnormal neurotransmissions. At present, most scholars believe deregulated liver functions and impaired CNS functions can influence each other, resulting in secondary damages to the body [3,37] . Recent study found that increased activity of brain acetylcholinesterase in patients and animals of type C HE would cause the decrease of acetylcholine level.…”
Section: Type C He: Animal Models and Pathogenic Mechanismsmentioning
confidence: 99%
“…It is based on changes of consciousness, intellectual function, behavior, and is useful in monitoring patient progress. Ammonia levels should be measured if HE is suspected and lactulose and systemic antibiotcs prescribed to alter gut flora and reduce the production and absorption of ammonia [80] . A number of risk factors have been identified for the development of post-hepatectomy liver failure and have been summarised in a recent review [81] .…”
Section: Bile Leaksmentioning
confidence: 99%
“…It is observed in patients with decompensated liver function such as in Cirrhosis and in those with Acute Liver Failure [ALF], in the absence of other known brain disease [1] . HE can be a complication after insertion of a trans-jugular intrahepatic porto-systemic shunt [TIPS] [2] .…”
Section: Introductionmentioning
confidence: 99%